The object-oriented thought process - Weisfeld, Matt A. (Developer's library., 2004)
A new edition of this title is available, ISBN-10: 0672330164 ISBN-13: 9780672330162 The Object-Oriented Thought Process, Second Edition will lay the foundation in object-oriented concepts and then explain how various object technologies are used. Author Matt Weisfeld introduces object-oriented concepts, then covers abstraction, public and private classes, reusing code, and devloping frameworks. Later chapters cover building objects that work with XML, databases, and distributed systems (including EJBs, .NET, Web Services and more). Throughout the book Matt uses UML, the standard language for modeling objects, to provide illustration and examples of each concept.